The Repositioning of Campus as a Cultural Movements Engine in the Eradication of Corruption - RR Dewi Anggraeni; Bachtiar Bachtiar; Iman Imanuddin (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
At the theoretical and historical level, the campus has always been a symbol of resistance to all forms of deviation, without exception for efforts to fight corruption as an extraordinary crime. Morally, the campus has an enormous responsibility to ensure and guarantee that Mother Earth is free from all corrupt practices. Even so, the campus is not a sterile area for corrupt practices. This study used a qualitative research method with a statutory approach. The results of the study state that corruption has penetrated into the joints of the life of the academic community, which should actually play a role as a locomotive in eradicating corruption. Recognizing that the corruption virus has spread among the academic community, it is urgent to reposition the role of the campus in the fight against corruption. Repositioning the role of the campus can be started from (i) aspects of the tri dharma of higher education, (ii) administrative aspects, and (iii) exemplary aspects. Repositioning the role of the campus should be done considering that the campus with the characteristics of its value-oriented academic community is believed to be the best place to teach and instill anti-corruption values as an ongoing cultural movement. The cultural movement has made the campus a laboratory for the process of institutionalizing anti-corruption values, principles, and morality. In the long term, this movement will become a culture that can free the nation's leading cadres from corrupt behavior and mentality.